Mobile Phone and Internet Use Mostly for Sex-Seeking and Associations With Sexually Transmitted Infections and Sample Characteristics Among Black/African American and Hispanic/Latino Men Who Have Sex With Men in 3 US Cities. Issue 5 (May 2017) - Allen, Jacob E.; Mansergh, Gordon; Mimiaga, Matthew J.; Holman, Jeremy; Herbst, Jeffrey H.
Abstract : Background: Men who have sex with men (MSM) have a relatively high prevalence of sexually transmitted infections (STIs). This study examines the association of self-reported STIs and use of mobile phones and/or computer-based Internet to meet sexual partners among black and Hispanic/Latino MSM in the United States. Methods: Black and Hispanic/Latino MSM (N = 853) were recruited from 3 US cities (Chicago, IL; Kansas City, MO; and Fort Lauderdale, FL) via online and community outreach. Men completed a computer-assisted, self-interview assessment on demographics, use of mobile phones and computer-based Internet for sex-seeking, sexual risk behavior, and self-reported bacterial STIs in the past year. Multivariable logistic regression was used to model independent associations of STIs and use of these technologies to meet sexual partners. Results: Twenty-three percent of the sample reported having an STI in the past year; 29% reported using a mobile phone and 28% a computer-based Internet mostly for sex-seeking; and 22% reported using both. Number of male sexual partners (past year) was associated with any STI (adjusted odds ratio, 1.03; 95% confidence interval, 1.01–1.06). Adjusting for human immunodeficiency virus status, number of male sexual partners (past year), and demographic variables, men who reported use of both mobile phones and computer-based Internet for sex-seeking had increased odds of reporting an STI (adjusted odds ratio, 2.59; 95% confidence interval, 1.75–3.83), as well as with separate reports of chlamydia, gonorrhea, and syphilis ( P 's < 0.05). Conclusions: Enhanced community education regarding STI prevention, testing, and treatment options are necessary among this subpopulation of MSM who may benefit from messaging via Internet and mobile phone application sites. Abstract : A study of black and Hispanic/Latino men who have sex with men found that use of both mobile phones and computer-based Internet mostly for sex-seeking was associated with self-reported sexually transmitted infections in the past year.